The Impact of the SVB Collapse on Banking Industry - Xi, Ye (2023)
A Master of Science thesis in Finance by Ye Xi entitled, “The Impact of the SVB Collapse on Banking Industry”, submitted in November 2023. Thesis advisor is Dr. Anis Samet and thesis co-advisor is Dr. Kimberly Gleason. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).